Suspect and non-target screening of acutely toxic Prymnesium parvum - Taylor, Raegyn B. (Sci Total Environ, 2020)
Harmful algal blooms (HABs) are increasing in frequency, magnitude, and duration around the world. Prymnesium parvum is a HAB species known to cause massive fish kills, but the toxin(s) it produces contributing to this acute toxicity has not been confirmed. In the present study, a 2 X 2 factorial design was employed to examine influences of salinity (2.4 or 5 ppt) and nutrient limitation (f/2 or f/8) on P. parvum acute toxicity to fish and produced molecules. Acute toxicity (LC(50)) of these cultures, following a 48-hour mortality assay, ranged from 10,213 to 96,816 cells mL(−1). Non-targeted analysis was performed using liquid chromatography high-resolution mass spectrometry (LC-HRMS) to investigate compounds contributing to the differential toxicological responses. When P. parvum elicited toxicity to fish, suspect screening confirmed the presence of several prymnesins, and the peak area of PRM-A (3 Cl; prymnesin2(aglycone)) was significantly (p < 0.05) and positively related to acute toxicity. In addition, a non-targeted approach to highlighting peaks that differ between two chemical fingerprints was developed, termed a relative difference plot, and used to search for peaks co-varying with P. parvum acute toxicity. Several peaks were highlighted along with the prymnesins identified through suspect screening when acute toxicity to fish was observed.